Gender Inequalities in Access to the Right to Education: The Consequences of the Taliban’s Gender-based Educational Policy on Women in Afghanistan - Mohammad Ayub Yusufzai; Geeta Ravi Kumar (حقوق بشر)
Since the Taliban's second takeover, Afghan women have faced significant threats to access to the right to education. The Taliban's gender-based policies hinder their right to equal and quality educational opportunities. This research article critically examines the existence of gender inequalities in women's access to the right to education, with a specific focus on the consequences of the Taliban's gender-based educational policies. The study employs a phenomenological approach, combining qualitative and desk methods, to comprehensively analyze the situation. Drawing on primary data collected through a questionnaire, this research presents an understanding of the factors affecting women due to the exclusion of women from access to education. it was found that the Taliban policies on education are based on gender. Gender inequality is the key to educational policies. The gender-based policy of the Taliban made women inferior to men and excluded them from the right to education. The study identifies that the policy of women's exclusion from the right to access education had major harmful consequences for Afghan women. The major consequences are the exclusion of women from society, increased unemployment among women, increased poverty among women who were the breadwinners of their houses, increased use of violence by men, forced marriages, psychological distress and depression, increased illiteracy rate among women, and masculinization of the policies and norms in the society.